2013
DOI: 10.1101/lm.031740.113
|View full text |Cite
|
Sign up to set email alerts
|

Learned together, extinguished apart: reducing fear to complex stimuli

Abstract: Pairing a previously neutral conditioned stimulus (CS; e.g., a tone) to an aversive unconditioned stimulus (US; e.g., a footshock) leads to associative learning such that the tone alone comes to elicit a conditioned response (e.g., freezing). We have previously shown that an extinction session that occurs within the reconsolidation window attenuates fear responding and prevents the return of fear in pure tone Pavlovian fear conditioning. Here we sought to examine whether this effect also applies to a more comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 51 publications
2
21
1
Order By: Relevance
“…Although others have demonstrated that postretrieval extinction can prevent fear relapse in animals (Auchter et al, 2017; Baker et al, 2013; Clem & Huganir, 2010; Flavell et al, 2011; Jones et al, 2013; Jones & Monfils, 2016; Monfils et al, 2009; Olshavsky et al, 2013; Rao-Ruiz et al, 2011; Shumake & Monfils, 2015) and in humans (Agren et al, 2012a, 2012b, 2017; Björkstrand et al, 2015; Golkar et al, 2017; Liu et al, 2014; Meir Drexler et al, 2014; Meir Drexler & Wolf, 2016a; Oyarzún et al, 2012; Schiller et al, 2010, 2013; Thompson & Lipp, 2017), it is important to consider that prevention of relapse may not equate to erasure of the fear memory. For example, a well-trained extinction memory may be able to outcompete a fear memory for expression, without the fear memory necessarily being eliminated (Lattal & Wood, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although others have demonstrated that postretrieval extinction can prevent fear relapse in animals (Auchter et al, 2017; Baker et al, 2013; Clem & Huganir, 2010; Flavell et al, 2011; Jones et al, 2013; Jones & Monfils, 2016; Monfils et al, 2009; Olshavsky et al, 2013; Rao-Ruiz et al, 2011; Shumake & Monfils, 2015) and in humans (Agren et al, 2012a, 2012b, 2017; Björkstrand et al, 2015; Golkar et al, 2017; Liu et al, 2014; Meir Drexler et al, 2014; Meir Drexler & Wolf, 2016a; Oyarzún et al, 2012; Schiller et al, 2010, 2013; Thompson & Lipp, 2017), it is important to consider that prevention of relapse may not equate to erasure of the fear memory. For example, a well-trained extinction memory may be able to outcompete a fear memory for expression, without the fear memory necessarily being eliminated (Lattal & Wood, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This paradigm was found to result in a persistent reduction in fear expression, possibly suggesting that the original fear memory had been updated. This paradigm has been replicated several times in both non-human animals39404142434445464748 and humans49505152535455. However, there is a large degree of individual variability in extinction alone, and equally as much (if not more) variation in the retrieval + extinction paradigm.…”
Section: Fear Extinctionmentioning
confidence: 99%
“…One of the most studied forms of reconsolidation-dependent memory updating is the reconsolidation-update procedure in which an isolated retrieval event is followed by a massed extinction session (Monfils et al, 2009). This precise spacing of reconsolidation and extinction procedures results in a persistent attenuation of fear responses to specific cues in both rodents (Baker, McNally, and Richardson, 2013; Jones, Ringuet, and Monfils, 2013; Pineyro, Ferrer Monti, Alfei, Bueno, and Urcelay, 2013) and humans (Oyarzun et al, 2012; Schiller, Kanen, Ledoux, Monfils, and Phelps, 2013; Schiller et al, 2010; Warren et al, 2013) and is regulated by dynamic changes in AMPA receptor expression (Clem and Huganir, 2010; Rao-Ruiz et al, 2011). However, while this reconsolidation-update procedure is effective at attenuating fear responses to newer memories, the paradigm is much less effective with older memories (Clem and Huganir, 2010).…”
Section: Epigenetic Regulation Of Memory Reconsolidationmentioning
confidence: 99%